Reliability and Validity of the Full-Length Greek-Cypriot Version of the Children's Depression Inventory 2 - Alexandrou, George; Karanikola, Maria; Chatzittofis, Andreas; Sokratous, Sokratis (My University, 2025)
Childhood depression has become a serious concern in recent years. Therefore, it is important for healthcare professionals to have a reliable instrument for measuring depressive symptoms adapted to their culture and language. The Children's Depression Inventory 2 (CDI-2) is a tool that has been widely used in many countries. The present study aimed to investigate the internal consistency reliability and construct validity of the full-length 28-item Greek-Cypriot version of the CDI-2: Self Report (CDI-2:SR) among schoolchildren in Cyprus.
Keywords: Child Depression